Simplified analysis techniques for VLF wave propagation in the earth–ionosphere waveguide. Issue 1 (22nd January 2013) - Itoh, Hitoshi; Ando, Yoshiaki; Hayakawa, Masashi
Abstract VLF (very low frequency; 3 to 30 kHz) wave propagation in the earth–ionosphere waveguide can be simply analyzed by the method developed in this paper. The finite‐diﬀerence time‐domain (FDTD) method is used with a conductivity tensor to model the ionosphere, and the applicability is limited to monotonic cases. The proposed method is compared with the wideband method, and it is concluded that the newly developed method can be used as a VLF wave simulator without errors. Conformal FDTD is also introduced to allow for the curvature of the earth's surface, and we have clarified the diﬀerence between two‐dimensional modeling in Cartesian coordinates and cylindrical coordinates. © 2013 Wiley Periodicals, Inc. Electr Eng Jpn, 183(1): 25–31, 2013; Published online in Wiley Online Library (wileyonlinelibrary.com). DOI 10.1002/eej.22302